Pembuatan Mural sebagai Sarana Pengembangan Seni Visual dan Strategi Promosi pada Universitas Potensi Utama - Rendy Prayogi; Mhd. Rusdi Tanjung; Fhery Agustin; Nazwa Nabila Batubara (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
This community service activity aims to develop students’ visual art skills and strengthen the institutional image of Universitas Potensi Utama through the creation of a mural on the university campus. The mural was chosen as a medium due to its ability to convey educational messages, build visual identity, and enhance public spaces effectively. Involving lecturers and students from the Visual Communication Design program, the project was carried out in several stages: concept planning, sketching, coloring, and finishing. The final result is a 2.5 x 31-meter mural that illustrates the spirit of education, cultural diversity, and innovation. The outcomes of this activity include improved technical and collaborative skills among students, enhanced campus visual identity, and increased appreciation for murals as a medium of visual communication. Thus, this initiative not only contributes to the campus aesthetics but also serves as an effective institutional promotion strategy through participatory art.